Applying Project-Based Learning to Improve Vocational English Skills - Sulamit Syeba; Debora Debora; Susanti Susanti; Dinny Aminarti; Auginae Maria Victoria (FKIP Universitas Palangka Raya, 2026)
A common problem in teaching English in vocational secondary schools (SMK) is the mismatch between the curriculum taught and the needs of the job market. The English learning process in SMKs differs from that in general schools, as writing, reading, speaking and listening skills are an integral part of the educational experience in vocational schools, especially in vocational English programmes. One method used to improve English skills is Project-based Learning (PjBL), which is designed to challenge students to solve real problems often encountered in the tourism industry. The purpose of this study is to implement PjBL, specifically in the Tourism department, to improve English skills and understanding of tourism services, planning, and authentic experiences, which ultimately result in products such as brochures. This research employed the Classroom Action Research method with two cycles: planning, action, observation, and reflection. To measure the effectiveness of the programme, pre-tests and post-tests were conducted. The results of cycle 1 showed that PjBL implementation was 67% because teachers and students were still adapting to this learning model. However, in cycle 2, implementation increased to 94.4%, exceeding the minimum target of 80%. The level of student engagement was recorded at 81.25%, and most of the post-test scores were in the range of 70–80. The use of PjBL in English language learning at vocational schools for tourism proved to be effective in improving students' English skills, while also developing critical thinking, collaboration, and creativity skills that are relevant to the current needs of the tourism industry.